Karakteristik Mekanisme Koping Pasien Kanker Payudara di Poli Bedah Onkologi Rumkital Dr. Ramelan Surabaya - Nur Muji Astuti; Dya Sustrami; Puji Hastuti; Lela Nurlela; Fransiska Herningtiyas A.N (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
Breast cancer is the growth of uncontrolled malignant cells in abnormal cells of breast tissue (Osborn, Kathleen Swraa 2010). The patient's coping mechanisms are important to deal with the existing stressors and will have an impact on the anxiety levels facing the patient. Koping can suppress the stressors faced by the patient. The patient's coping mechanisms are important to deal with the existing stressors and will have an impact on the anxiety levels facing the patient. Coping can suppress the stressors faced by the patient so that it can decrease the anxiety level of breast cáncer patients (Gaston-johansson et al. 2013). This research used cross sectional design. The population was taken in oncology dr. Ramelan Hosptal Surabaya. Data collection used a demographic data questionnaire and a COPE Brief questionnaire with medium and low grade coping categories. The results showed that most of the respondents use coping mechanism which is problema oriented that is 21 people (60,0%), 4 people (11,4%) emotion oriented and 10 people (28,6%) oriented to problem and emotion. Coping Mechanism patients who were under going treatment at Rumkital Dr Ramelan Hospital Surabaya place oriented to the problem. Nurses were expected to improve their ability to improve breast cancer patients' coping with peer grouping. Keywords: Coping Mechanism, Breast Cancer